The Role of the Principal as a Leader in Shaping Effective Schools: A Multi-case Study at MAN 1 Tulungagung and SMAN 1 Kedungwaru - Kusmaduni, Fati’ah; Akhyak, Akhyak; Maunah, Binti (International Journal of Science, Technology & Management, 2026)
This study aims to investigate the determinant role of the principal as a leader in reconstructing a quality culture towards an effective school. Employing a qualitative approach with a multi-case study design, the research was conducted at two sites with distinctive characteristics: MAN 1 Tulungagung (based on religious values) and SMAN 1 Kedungwaru (based on professional-secular standards). Data were collected through in-depth interviews, participant observation, and documentation studies, which were then analyzed using the interactive model by Miles, Huberman, and Saldana. The results reveal a substantive finding in the form of a "Hybrid-Integrative Leadership Model" that synergizes three strategic roles cyclically. First, as a Motivator, the principal builds teacher resilience through distinct approaches: Spiritual-Paternalistic Leadership (worship-value based) in the Madrasah and Instructional-Technocratic Leadership (meritocracy-based) in the public school. Second, as an Innovator, the principal acts as a system architect who institutionalizes change ideas into strategic documents and organizational culture. Third, as an Administrator, the principal serves as a strategic risk manager who dares to make calculated decisions for resource efficiency. The study concludes that school effectiveness does not arise from a single managerial adoption, but from the principal's ability to orchestrate humanist flexibility and systemic firmness adapted to local wisdom.